Notch signaling sculpts the stem cell niche - Zamfirescu, Ana-Maria; Yatsenko, Andriy S.; Shcherbata, Halyna R. (Frontiers in Cell and Developmental Biology, 2022)
Adult stem cells depend on their niches for regulatory signaling that controls their maintenance, division, and their progeny differentiation. While communication between various types of stem cells and their niches is becoming clearer, the process of stem cell niche establishment is still not very well understood. Model genetic organisms provide simplified systems to address various complex questions, for example, how is a stem cell niche formed? What signaling cascades induce the stem cell niche formation? Are the mechanisms of stem cell niche formation conserved? Notch signaling is an evolutionarily conserved pathway first identified in fruit flies, crucial in fate acquisition and spatiotemporal patterning. While the core logic behind its activity is fairly simple and requires direct cell–cell interaction, it reaches an astonishing complexity and versatility by combining its different modes of action. Subtleties such as equivalency between communicating cells, their physical distance, receptor and ligand processing, and endocytosis can have an effect on the way the events unfold, and this review explores some important general mechanisms of action, later on focusing on its involvement in stem cell niche formation. First, looking at invertebrates, we will examine how Notch signaling induces the formation of germline stem cell niche in male and female Drosophila. In the developing testis, a group of somatic gonadal precursor cells receive Delta signals from the gut, activating Notch signaling and sealing their fate as niche cells even before larval hatching. Meanwhile, the ovarian germline stem cell niche is built later during late larval stages and requires a two-step process that involves terminal filament formation and cap cell specification. Intriguingly, double security mechanisms of Notch signaling activation coordinated by the soma or the germline control both steps to ensure the robustness of niche assembly. Second, in the vast domains of mammalian cellular signaling, there is an emerging picture of Notch being an active player in a variety of tissues in health and disease. Notch involvement has been shown in stem cell niche establishment in multiple organs, including the brain, muscle, and intestine, where the stem cell niches are essential for the maintenance of adult stem cells. But adult stem cells are not the only cells looking for a home. Cancer stem cells use Notch signaling at specific stages to gain an advantage over endogenous tissue and overpower it, at the same time acquiring migratory and invasive abilities to claim new tissues (e.g., bone) as their territory. Moreover, in vitro models such as organoids reveal similar Notch employment when it comes to the developing stem cell niches. Therefore, a better understanding of the processes regulating stem cell niche assembly is key for the fields of stem cell biology and regenerative medicines.